BAJUBÁ: “linguagem” como traço identitário do segmento LGBT - SANTOS, Eline Samara de Souza (UNIFAP – Universidade Federal do Amapá, 2022)
Starting from methodological assumptions that articulate the study on sexuality (FOUCAULT, 1998: FRY; MACRAE, 1985) identity (MOITA LOPES, 2002, 2006) and Analysis Critical Discourse henceforth ADC (FAIRCLOUGH, 2001; RESENDE; RAMALHO, 2006; MELO, 2009), is research aims to present the construction of relevant identity for studies in Applied Linguistics (LA), in addition to analyzing the Bajuba – language originated by the union of several African languages with Brazilian Portuguese, which began to be used initially by transvestites who attended the yards of Candomblé and subsequently throughout the LGBT community – as a discursive practice, socio-culturally constructed, which acts as a defense mechanism, resistance and social identity of self-assertion and language of a segment historically oppressed and stigmatized. For the development of goals, there was the application of questionnaires, observation and recording interviews with six people from Amapaense Lesbian Federation, Gay, Bisexual, and Transgender (FALGBT) and 4 people from the Federal University of Amapá (UNIFAP). By the use of these instruments, it was found in the data analysis, the relationship between Bajuba and linguistic components of african-Brazilian rites, as well as confirming that this language is presented as identity constitution LGBT in which allows a free and dynamic interaction sociability, in many different subjects and environments, where they can not be understood by certain individuals which are around them.